Diversity for development: highlights of IPGRI's strategy - International Plant Genetic Resources Institute (1999)
This brochure contains a summary of IPGRI's strategy for 1999-2004 ”Diversity for Development”. It outlines IPGRI's tasks, mission, objectives and strategic choices.